Determination of Optimum Moisture Content of Palm Nut Cracking for Efficient Production of Whole Kernel - O. O. Antia; W. Olosunde; O. Offiong (Nigerian Journal of Technological Development, 2014)
After processing the palm fruit for oil, the nut is usually dried in order to loosen the kernel from the shell. The drying is necessary to enhance the release of whole kernel when the nut is cracked. A study was carried out to determine the optimum moisture content of nuts for high yield of whole kernels during cracking. Thirteen identical groups of fresh palm nuts with 240 nuts per group were subjected to oven drying at a temperature of 105 oC. Before starting, the initial mass of each nut was noted and at 2 h-intervals, a group was randomly selected and each of the 240 nuts cracked by impact after weighing for the determination of the nut moisture content. The nuts in the last group were cracked after a drying time of 26 h. The percentage of cracked nuts yielding whole kernels after impact cracking was used to determine the optimum moisture content the average value of which was 2.5% wet basis or 2.57% dry basis. At this moisture content the proportion of evaporable water retained in the intact nuts was estimated to be about of 11.2%. At the optimum moisture content, 84.2% of the cracked nuts yielded whole kernels. The optimum moisture content was obtained after a drying time of about 18 h.